Evaluate English Language and Communication Skills (ELCS) of Engineering Students through Cell Phone Assisted: An empirical study - Dandu, Ganesh; Mohana Charyulu, Gomatam; M , Latha (International Journal of Psychosocial Rehabilitation, 2020)
In the current academic scenario, engineering students are completely addicted to Android cell phones. These cell phones in the hands of each graduate have turned into an essential piece of their life; without these smart phones, they can't imagine their life. Teachers and parents restrict them from conveying cell phones into the classrooms for the reason that such devices cause interruptions and also are the way for deviation from focusing on the lecture. Here are some possible outcomes to transform this interest in utilizing the cell phones into an enthusiasm for learning languages and test their language abilities. One such probability is presenting them to various devices accessible for learning English through applications based on tests.The present study is focused on evaluating the ELCS of engineering graduates using cell phone-assisted language learning (CALL) tests, which are online devices. These tests assess the English language proficiency of engineering graduates and give them confidence to enhance their language. This paper revealed the advantages of assist cell phones for acquiring the skill benefit, firstly in developing the engineering graduate students’ English Language and Communication Skills. Outcomes of online tests are explored in this article. The article ends with the results of the assessments and some suggestions for progress. Students must be exposed to available online tools, and the most important one is to improve their ELCS.